Submarine Communication Cables and the Law of Armed Conflict: Some Enduring Uncertainties, and Some Proposals, as to Characterization. (21st April 2022) - McLaughlin, Rob; Paige, Tamsin Phillipa; Guilfoyle, Douglas
Abstract: Submarine data cables are of fundamental strategic consequence. However, two intensely context-sensitive and contemporary sets of questions about how these cables are to be dealt with by the law of armed conflict remain—questions which state practice during the two World Wars either did not resolve or did not need to address. Through an examination of the relevant legal history and current law, this article seeks to explore potential answers to these question sets. The first question set relates to the general approach to be adopted when dealing with submarine data cables within LOAC: a sui generis regime; discrete analogy; or general principles? The second question set addresses three lingering queries regarding legal characterization of submarine data cables for LOAC purposes, namely: (i) Are they ordinary military objectives? (ii) Can they be considered neutral objects? (iii) How do we assess proportionality in relation to attack on submarine data cables? The analysis concludes that a modified application of the ordinary rule of proportionality in LOAC targeting, noting some of the difficulties surrounding the concepts of incidental damage in this context, offers the most useful way forward.